Strategies to prevent delinquency among children and adolescents based on the central role of the school - Mohammadi Farsani, Iman; Malmir, Mahmoud; Ashrafi, Mahmoud; Heydari, Masoud (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: childhood and adolescence are of the important periods of life in which personality formation takes place. Therefore, the aim of the current research was to provide solutions to prevent delinquency among children and adolescents, relying on the central role of the school. Methods: The current research is analytical-descriptive and review. Therefore, the required data was collected in a library manner and the data was analyzed by reviewing the research literature. Results: among the institutions in which a person is a member are the family institution and the school institution. Children and teenagers spend most of their time in school, so if the school has special programs to guide and shape their personality, they can prevent this very vulnerable group from falling into various crimes and delinquencies. Therefore, the prevention of delinquency of children and adolescents in school has to return to the correct education and training programs established in the school. Conclusion: The findings indicate that the cooperation between the family and the school in a purposeful and organized manner and with sufficient understanding of education issues, mutual roles and rights and by benefiting from each other's capacities can be the foundation for proper education and prevention of delinquency.